Navigating the HIV Care Cascade: Addressing Challenges and Enhancing Outcomes - I Made Moh Yanuar Saifudin; Radian Ilmaskal; Rinaldi Daswito; Besral (RRZ Scientific Publishing, 2023)
Individuals living with HIV undergo a multifaceted and prolonged care process marked by clinical, social, and emotional complexities. Unfortunately, they often encounter stigma in various forms. This editorial paper delves into specific social and public health challenges, emphasizing the significance of healthcare providers actively involving patients in the intricacies of the HIV care cascade. By addressing these barriers, we aim to enhance patient engagement and ultimately improve the overall outcomes of HIV care.